Peran Penyidik Unit Narkoba Terhadap Analisa Pembuktian Sampel Darah Dalam Perkara Tindak Pidana Narkotika Dan Psikotropika - Bambang Hartono (PRANATA HUKUM, 2011)
The investigators role of drugs unit in blood sample analysis of evidence criminal narcotics and psychotropic, the process of examination of blood samples based on the Healthy Minister Decision No. 923IMenkes/SK/X/12009 on Technical Guidelines for Laboratory Investigation Narcotic Drugs and Psychotropic. The implementation of role, founded obstacle is: constraints on evidentiary analysis of blood samples in case of narcotic and psychotropic crime, among others: investigators were given 4 days, investigators here have difficulties because the examination of blood samples must be made at firensic laboratory in Jakarta, which takes a long time especially if conditions are unfavorable, limited personnel from Lampung Regional Police Drug Unit; legal culture of society, people seem less concerned with the abuse of narcotics. The power forensic results of blood samples as mail proof tool.